Authentication of Kaffir Lime Leaf Oil (Citrus hystrix D.C.) in Products Using FTIR Combined with Chemometrics - Jeffry, Jeffry; Guntarti, Any; Salamah, Nina (Pharmaceutical Sciences and Research, 2025)
Indonesia is rich in aromatic plants, producing approximately 40 types of essential oils used in various industries, including health and aromatherapy. Essential oils have significant potential but face high rates of adulteration. This study aimed to identify kaffir lime leaf oil (Citrus hystrix D.C.), to determine the essential oil profile, and to detect adulteration in commercial oil products. The methods used involved steam distillation and characterization tests of kaffir lime leaf essential oil, including yield percentage and organoleptic, density, refractive index, and solubility in alcohol. An essential oil content test and adulteration detection using FTIR combined with chemometrics were also conducted. The FTIR results showed distinctive peaks for kaffir lime leaf oil, allowing the identification of the main compounds in the oil. Multivariate analysis using the PLS model could predict oil adulteration with RMSEC 1.319, RMSECV 1.913, and RMSEP 2.362, indicating the model’s accuracy. Furthermore, PCA successfully separated and grouped the tested oils. This study concludes that the analyzed oil was kaffir lime leaf oil, based on the characterization results and FTIR spectra showing distinctive peaks of the oil. PLS and PCA analysis showed that the three tested commercial oil products did not contain turpentine adulterants.